A review of lasers and light for the treatment of onychomycosis. Issue 2 (24th December 2013) - Ortiz, Arisa E.; Avram, Mathew M.; Wanner, Molly A.
<x xml:space="preserve">Abstract</x> Background and Objective Onychomycosis is a common fungal infection that affects many individuals. Systemic therapies are effective, but are limited by their side effects and potential for hepatotoxicity. Topical therapies have less serious side effects, yet provide only limited efficacy due to their inability to penetrate the nail plate. These limitations have led to the investigation of laser and light‐based modalities as alternative treatment options for onychomycosis. This article will provide an overview and critical assessment of the field of laser and other energy‐based treatments for onychomycosis. Study Design/Materials and Methods A literature search was conducted on laser and light‐based treatments for onychomycosis. Results Early data are promising, however, many of these studies are small or poorly designed. Conclusion Further evaluation and larger studies are needed to determine the optimal light source, pulse duration, and treatment schedule for long‐term success. Lasers Surg. Med. 46:117–124, 2014. © 2013 Wiley Periodicals, Inc.